Ondel-Ondel sebagai Ikon Seni Tradisi Betawi - syaekhu rakhman; Yeni Handayani; Arief Hidayat (CHRONOLOGIA, 2023)
Indonesia is a country with many different tribes and cultures. Each region has its own characteristics that will be imprinted in the memory of each individual, which will eventually become an icon of a particular area. One of the city's icons is Ondel-Ondel from Betawi. Ondel-Ondel are giant dolls that are understood by the Betawi people as sacred culture and are used in ritual sacrifices to ancestral spirits. At first Ondel-Ondel was created as a way to repel reinforcements from the Betawi tribe. However, now everything is different. Ondel-Ondel is no longer considered sacred. The existence of Ondel-Ondel art is no longer used for cultural activities but is misused in street activities. This means that there has been a change in this Betawi Ondel-Ondel art. These changes are caused by social conditions. This is why efforts to increase awareness of local culture need to be increased. Changing times have formed new patterns of thinking about things that are traditional and not all people know the meaning behind the Betawi Ondel-Ondel art. The research method used is a qualitative method, data collection is done through literature studies, observations and interviews.